A DSSC Electrolyte Preparation Method Considering Light Path and Light Absorption - Jianjun Yang; Jiaxuan Liu; Yaxin Li; Xiaobao Yu; Zichuan Yi; Zhi Zhang; Feng Chi; Liming Liu (Micromachines, 2022)
The electrolyte is one of the key components of dye-sensitized solar cells’ (DSSC) structure. In this paper, the electrolyte formulation of a new DSSC with external photoanode structure was studied. Based on the idea that the electrolyte should match the light absorption and light path, iodine series electrolytes with different concentrations were configured and used in the experiment. The results showed that the external photoanode structure solar cells assembled with titanium electrode had the best photoelectric conversion ability when the concentration of I2 was 0.048 M. It achieved the open circuit voltage of 0.71 V, the short circuit current of 8.87 mA, and the filling factor of 57%.